Journal of the Entomological Society of British Columbia - Entomological Society of British Columbia (Entomological Society of British Columbia, 1966)
"The JESBC is an open-access journal. Articles are published online as they are accepted; bound copies are printed every December. Manuscripts dealing with all facets of the study of arthropods will be considered for publication. Submissions may be from regions beyond British Columbia and the surrounding jurisdictions provided that content is applicable or of interest to a regional audience."--Journal's website.
Keywords: Insects : British Columbia : Periodicals; Insect pests : British Columbia : Periodicals; Insectes : Colombie-Britannique : Périodiques; Insectes nuisibles et utiles : Colombie-Britannique : Périodiques; Insectes nuisibles : Colombie-Britannique : Périodiques; Insect pests; Insects; British Columbia